1970
DOI: 10.3126/njog.v4i1.3330
|View full text |Cite
|
Sign up to set email alerts
|

General practitioner and obstetric service in rural Nepal: A way forward

Abstract: Aims: To review different types of obstetric services provided by the general practitioners with a back-up ofpara-medical staffs in a rural Nepal to analyze obstacles faced in providing qualitative care.Methods: Retrospective analysis of all deliveries conducted at Okhaldhunga Community Hospital in oneyear duration (December 2005 to December 2006).Results: In the study period, 123 deliveries took place with 126 births due to the result of three sets of twin.Caesarean were done in 28(22.7%) and most of them bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A study in BH’s catchment area demonstrated institutional capacity and distance from home to be key factors influencing women’s decisions regarding home vs institutional birth [ 14 ]. In a single-facility study in rural Nepal, 93% of cesarean sections were performed on an emergency basis [ 22 ], supporting the notion that presentations are often late, and timely referrals are infeasible in the remote hills of Nepal.…”
Section: Discussionmentioning
confidence: 90%
“…A study in BH’s catchment area demonstrated institutional capacity and distance from home to be key factors influencing women’s decisions regarding home vs institutional birth [ 14 ]. In a single-facility study in rural Nepal, 93% of cesarean sections were performed on an emergency basis [ 22 ], supporting the notion that presentations are often late, and timely referrals are infeasible in the remote hills of Nepal.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, incorporating GPs into obstetric services is seen as a means to enhance maternal healthcare in rural Nepal. [2][3][4] GPs are already leading most of the district-level hospitals in Nepal, providing holistic primary health care. This primary health care model led by GPs is identified as an effective platform for addressing Non-Communicable Diseases (NCDs) through preventive and curative interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In some areas, General Practitioners (GPs) are providing primary health care including basic surgical care and caesarean sections. 1,2 We have no criteria to test GPs about their surgical abilities and to allow them to perform certain type of surgeries. We lack the national data about how many major surgeries are being performed by GPs.…”
mentioning
confidence: 99%